Penerapan Terapi Rekreasi Seni Kerajinan Tangan Tingkatkan Kreativitas Pada Siswa-Siswi Kelas 2 di SDN Tarokan 4 Kediri (Prosiding SEMDIKJAR (Seminar Nasional Pendidikan dan Pembelajaran), 2025)
Recreational therapy is defined as a type of therapy that uses various recreational activities such as sports, hobbies, games, and tourism. In another source, it is mentioned that recreational therapy is therapy conducted during free time, aimed at allowing individuals to spend time constructively, enjoyably, and develop social skills. The purpose of this writing is to study and practice recreational therapy for children to enhance creativity. Craft recreational therapy was chosen because this activity can stimulate imagination, fine motor skills, and children's expression abilities through the creation of artwork. This community service method uses a descriptive design with a case study approach. This community service took place on June 17, 2025, at SDN 4 TAROKAN using 26 student samples. After conducting craft recreational therapy with the students, it is expected that they will understand and enhance their creativityIn this service, the author did not find any difficulties; students were happy to participate in recreational art therapy activities to enhance creativity. Thus, the application of recreational art therapy can be an effective alternative learning method in supporting the development of children's creativity in elementary schools.